Validation of the short form of the intercultural sensitivity scale (ISS-15). (November 2016) - Wang, Wenting; Zhou, Mingming
Abstract: Through the process of globalization, individuals are becoming increasingly interculturally sensitive and competent through exposure to cultural differences. To meet the growing empirical interest in intercultural communication competence and sensitivity, this study examined a short intercultural sensitivity measurement scale for use in contexts with limited time constraints. We abbreviated the 24-item Intercultural Sensitivity Scale to create a 15-item version (ISS-15). To permit its use in a non-English speaking culture, the ISS-15 was translated into Chinese and administered to university students in mainland China. Overall, the results indicated that the ISS-15 retained significant levels of reliability and validity. Confirmatory factor analyses showed that the short form fit the data better than the original form. The five subscales of the ISS-15 also showed acceptable internal consistency. Hence, the Chinese version of the ISS-15 was found to be valid and reliable for use in cross-cultural research settings with limited time constraints.